If #y'(x)+y(x)g'(x)=g(x)g'(x)" ; y(0)=0 ; g(0)=g(2)=0 " where " x in RR# then #y(2)=?#

Answer 1

#y(2)=-2#

This equation is of type

#y'+P(x)y=Q(x)#
Making #u(x)=int_(x_0)^xP(xi)d xi# we have
#d/(dx)(e^(u(x)) y)=e^(u(x))(y'+P(x) y) = e^(u(x)) Q(x)# so
#y = e^(-u(x))int_(x_0)^x e^(u(xi))Q(xi)d xi#
Here #P(x)= g'# so #u(x) = g(x)# and

#y=e^(-g(x))int_(x_0)^x g(xi) d/(d xi)(e^(g(xi)))d xi =e^(-g(x))(( g(x)-1)e^(g(x))+C)# or

#y = g(x)-1+Ce^(-g(x))#
Now, using the initial conditions, #y(0)=g(0)= 0# we have
#0=-1+C# so #C = 1# and
#y = g(x)-1+e^(-g(x))# and also
#y(2)=g(2)-1+e^(-g(2)) = 0#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To solve the given differential equation, we can use the method of integrating factors. Given ( y'(x) + y(x)g'(x) = g(x)g''(x) ), we'll first rewrite the equation as ( y'(x) + y(x)g'(x) - g(x)g''(x) = 0 ).

Now, we'll find the integrating factor, which is given by ( e^{\int P(x)dx} ), where ( P(x) ) is the coefficient of ( y(x) ), which is ( g'(x) ) in this case.

So, the integrating factor, ( I(x) = e^{\int g'(x)dx} ).

Integrating ( g'(x) ), we get ( g(x) ).

Therefore, the integrating factor becomes ( I(x) = e^{g(x)} ).

Now, we'll multiply both sides of the differential equation by the integrating factor:

( e^{g(x)}[y'(x) + y(x)g'(x) - g(x)g''(x)] = 0 ).

This simplifies to:

( e^{g(x)}[y'(x)e^{g(x)} + y(x)g'(x)e^{g(x)} - g(x)g''(x)e^{g(x)}] = 0 ).

Now, we recognize that the left-hand side can be written as the derivative of a product:

( \frac{d}{dx}[y(x)e^{g(x)}] = 0 ).

Integrating both sides with respect to ( x ), we get:

( \int \frac{d}{dx}[y(x)e^{g(x)}] dx = \int 0 dx ).

This simplifies to:

( y(x)e^{g(x)} = C ), where ( C ) is the constant of integration.

Given ( y(0) = 0 ), we have:

( y(0)e^{g(0)} = C ).

Since ( g(0) = 0 ), ( e^{g(0)} = 1 ), so ( C = 0 ).

Therefore, ( y(x)e^{g(x)} = 0 ).

Given ( g(2) = 0 ), we have:

( y(2)e^{g(2)} = 0 ).

Since ( g(2) = 0 ), ( e^{g(2)} = 1 ).

So, ( y(2) = 0 ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7